2011
DOI: 10.1007/s12028-011-9637-1
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Effects of Intraventricular Extension in Intracerebral Hemorrhage

Abstract: Hematoma extension to the third and fourth ventricle seems to cause profound autonomic dysregulation, possibly contributing to poor outcome. Patients with IVH in this location should be monitored vigorously to prevent and treat complications of autonomic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…Assessment of serial troponin I levels during hospital stay revealed a further increase in the rate of elevated troponin levels, a finding predominantly driven by increased ventricular involvement. As reported previously for patients with subarachnoid hemorrhage [21], elevation of troponin I levels may, on the one hand, result from intraventricular blood and, therefore, meningeal irritation, leading to strong systemic stress-responses [22,23]. As a result, an enhanced release of catecholamines and consequently higher myocardial stress may reflect a neurocardiac dysbalance, evident also after ICH, notably in those patients with intraventricular involvement [21,22,24].…”
Section: Discussionmentioning
confidence: 83%
“…Assessment of serial troponin I levels during hospital stay revealed a further increase in the rate of elevated troponin levels, a finding predominantly driven by increased ventricular involvement. As reported previously for patients with subarachnoid hemorrhage [21], elevation of troponin I levels may, on the one hand, result from intraventricular blood and, therefore, meningeal irritation, leading to strong systemic stress-responses [22,23]. As a result, an enhanced release of catecholamines and consequently higher myocardial stress may reflect a neurocardiac dysbalance, evident also after ICH, notably in those patients with intraventricular involvement [21,22,24].…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, the volume of blood within the ventricle is associated with outcome in IVH, and >20 ml of blood in the ventricle is independently associated with a worse outcome (Sumer et al 2002; Tuhrim et al 1999). Intraventricular hemorrhagic extension is more common when the focus of hemorrhage is adjacent to the ventricle, such as in the thalamus or caudate (Hallevi et al 2008; Sykora et al 2012). One study reported a 100% incidence of IVH in caudate ICH (Hallevi et al 2008).…”
Section: Therapeutic Targets and Ongoing Clinical Trialsmentioning
confidence: 99%
“…Large volume ICH and hypertension are also associated with intraventricular hemorrhagic extension (Pang et al 1986; Steiner et al 2006). In addition, the location of the hematoma in the 3 rd and 4 th ventricle may contribute to poor outcome by causing autonomic dysfunction (Hallevi et al 2012; Sykora et al 2012). …”
Section: Therapeutic Targets and Ongoing Clinical Trialsmentioning
confidence: 99%
“…Lee et al [97] also detected a higher incidence of intraventricular haemorrhage in the thalamic and basal ganglia. Intraventricular haemorrhage patients including the third and fourth ventricle or ICH patients with insular involvement are reported to have lower baroreflex sensitivity than the patients without these involvements, suggesting that involvement of these sites could contribute to impairment of autonomic blood pressure regulation [157, 158]. Hypertensive responses can be exaggerated and additive because of the impaired baroreceptor sensitivity [135].…”
Section: Acute Progressing Haemorrhagic Strokementioning
confidence: 99%